Engineered acetogenic bacteria as microbial cell factory for diversified biochemicals - Zhang, Jun-Zhe; Li, Yu-Zhen; Xi, Zhi-Ning; Gao, Hui-Peng; Zhang, Quan; Liu, Li-Cheng; Li, Fu-Li; Ma, Xiao-Qing (Frontiers in Bioengineering and Biotechnology, 2024)
Acetogenic bacteria (acetogens) are a class of microorganisms with conserved Wood-Ljungdahl (WL) pathway that can utilize CO and CO2/H2 as carbon source for autotrophic growth and convert these substrates to acetate and ethanol. Acetogens have great potential for the sustainable production of biofuels and bulk biochemicals using C1 gases (CO and CO2) from industrial syngas and waste gases, which play an important role in achieving carbon neutrality. In recent years, with the development and improvement of gene editing methods, the metabolic engineering of acetogens is making rapid progress. With introduction of heterogeneous metabolic pathways, acetogens can improve the production capacity of native products or obtain the ability to synthesize non-native products. This paper reviews the recent application of metabolic engineering in acetogens. In addition, the challenges of metabolic